Association between dietary choline intake and odds of preeclampsia: a case–control study - Zhu, Junhua; Bo, Yacong; Ma, Ruixue; Jiang, Ziwei; Wang, Jiahan; Yuan, Zheng; Zhao, Xianlan; Cao, Yuan; Duan, Dandan; Dou, Weifeng; Liu, Yanhua; Lyu, Quanjun (Frontiers in Nutrition, 2025)
BackgroundPreeclampsia (PE) is a leading cause of maternal and perinatal morbidity and mortality. Choline, essential in one-carbon metabolism and vascular function, may influence placental health. We examined associations of total, subtype-, and source-specific dietary choline with PE odds in Chinese women.MethodsWe conducted a 1:1 matched case–control study of 982 pregnant women (491 PE cases; 491 controls) in Zhengzhou, China. Dietary intake over the preceding three months was assessed using a validated semi-quantitative food-frequency questionnaire. Conditional logistic regression calculated odds ratios (ORs) and 95% confidence intervals (CIs) for total choline, lipid- vs. water-soluble forms, and animal- vs. plant-derived sources, adjusting for covariates. Restricted cubic splines explored possible non-linear dose–response associations.ResultsAmong 982 participants (491 PE cases; 491 controls), mean total choline intake was 335.8 mg/day, with eggs contributing 42.5%. In multivariable-adjusted models, compared with the lowest quartile, those in the highest quartile of total choline intake had 58% lower odds of PE (OR = 0.42; 95% CI, 0.26–0.68), with similar associations for lipid- (0.33; 0.22–0.48) and water-soluble forms (0.37; 0.25–0.54). Both animal- (0.43; 0.30–0.63) and plant-derived choline (0.31; 0.21–0.46) were protective, while their intake ratio was not. Each additional 25 g/day of egg (~half an egg) was linked to an 11% lower PE odds.ConclusionHigher habitual dietary choline intakes from animal and plant sources were independently associated with significantly lower odds of PE, suggesting that adequate, source-diverse choline intake in early pregnancy may offer a practical dietary strategy for PE prevention.